Fake News in Contemporary Communication Processes - Eduard E. Shults (RUDN Journal of Public Administration, 2022)
The article focuses on the phenomenon of fake news in contemporary communication processes. The article analyzes the characteristic features of fake news in terms of disinformation, interference by foreign actors, manipulation, media messages aimed at increasing demand. Fake news is considered from the standpoint of mediating society and the emergence of the concept of “media democracy”. The author concludes that the phenomenon of “fake news” becomes a structural concept in modern media, which is associated with the peculiarities of media and social psychology. This phenomenon fits into the peculiarity of modern society, which the French philosopher J. Baudrillard designated as a simulacrum.